Efficiency of Solar Cookers with Different Geometric Shapes Over the Last Decade: A Comprehensive Review - Lisma Dian Kartika Sari; Zainul Munawwir; Chairatul Umamah (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2024)
Mostly in rural areas in developing countries, biomass and fossil fuels are used for cooking. These fuels have negative impacts on the environment and human health. One solution to the problem is cooking using solar-powered stoves as a clean and environmentally friendly alternative energy. In this research, a literature study was conducted related to solar cookers which are divided into several types based on their geometric shape, namely box, parabolic, tube, and panel types. This research examines the performance of solar cookers, namely solar cooker efficiency (Î·%). In this literature study, the development of stoves from 2012 to 2023 has been reviewed and focused on. The sub-topics discussed revolve around the details of the geometry shape of the solar cooker on the performance of the solar cooker on the parameter of heat efficiency generated. The main conclusion of this review is that box-type solar cookers are more researched than other types of solar cookers, indicating that box-type solar cookers are more in demand and more economical in the manufacturing process. The highest average heat efficiency (Î·%) is produced by the tube-type solar cooker and the lowest is produced by the parabolic-type solar cooker. Other parameters also affect the efficiency of solar cookers, namely the intensity of solar radiation, the type of absorber/heat storage material, the use of reflectors with the right position (zenith and azimuth angles), the use of a tight cover pan (vacuum tube) for certain types of solar cookers and the length of cooking time.